Pengeluaran Pemerintah dan Pertumbuhan Ekonomi Regional: Studi Kasus Data Panel di Indonesia - Jamzani Sodik (Economic Journal of Emerging Markets, 2007)
The aim of this study is to examine the affect of government expenditure on regional economic growth by using the data of 26 provinces for periods of 1993-2003, and by applying GLS method (General Least Square) with panel data. Factors that affect the regional economic growth are private investment (Ip), government investment (Ig), government consumption (Cg), and labor force (L), we also identify other factors that can influence the regional economic growth. This variable is the rate openness economic provinces (X-M).The results found the regional economic growth for periods 1993-2003 is influenced by government investments (Ig), government consumption (Cg), labor force (L) and rate openness economic province (X-M). However, private investments (Ip) do not affect to regional economic growth. Keywords: private investments, government investments, government consumption, regional economic growth, and panel data